Soil‐structure interface modeling with the nonlinear incremental approach. (22nd April 2021) - Yang, Jie; Yin, Zhen‐Yu
Abstract: This paper aims to develop the nonlinear incremental modeling approach for describing both monotonic and cyclic behaviors of the soil‐structure interface. An exponential function is adopted as an example to reproduce the asymptotic relationship between the interface shear stress ratio and the shear displacement. A stress‐dilatancy relation is developed for the shear‐induced change of interface thickness. A shear stress reversal technique is incorporated for cyclic loading effect. Then, three numerical schemes for simulating constant thickness, constant normal load, and constant normal stiffness tests are established respectively. Next, three modifications are made to enhance the model by introducing a nonlinear shear modulus, the critical state concept, and the grain breakage effect. The enhanced model is evaluated with satisfactory performance in simulating interface tests under various loading conditions. Furthermore, the extensions to other nonlinear incremental interface model and clay‐structure interface modeling with rate effect relating to drainage conditions are successfully demonstrated and discussed.